Teaching Materials of Thematic Comics in the 2013 Curriculum Learning in Basic Schools - Sarkadi, Sarkadi; Alghozali, Muhammad Iqbal (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
Learning material books that are used today, especially in elementary schools (SD) are still full text, resulting in the low motivation of students to read them because they are not or not interesting. This study aims to develop thematic comics as learning materials in the 2013 Curriculum with the theme